Recession or resilience? Long-range socioeconomic consequences of the 17th century volcanic eruptions in northern Fennoscandia - H. Huhtamaa; M. Stoffel; C. Corona (Climate of the Past, 2022)
Past volcanic eruptions and their climatic impacts have been linked increasingly with co-occurring societal crises – like crop failures and famines – in recent research. Yet, as many of the volcanic cooling studies have a supra-regional or hemispheric focus, establishing pathways from climatic effects of an eruption to human repercussions has remained very challenging due to high spatial variability of socio-environmental systems. This, in turn, may render a distinction of coincidence from causation difficult. In this study, we employ micro-regionally resolved natural and written sources to study three 17th century volcanic eruptions (i.e., 1600 Huaynaputina, 1640/1641 Koma-ga-take–Parker, and 1695 unidentified) to look into their climatic and socioeconomic impacts among rural agricultural society in Ostrobothnia (Finland) with high temporal and spatial precision. Tree-ring and grain tithe data indicate that all three eruptions would have caused significant summer season temperature cooling and poor grain harvest in the region. Yet, tax debt records reveal that the socioeconomic consequences varied considerably among the eruptions as well as in time, space, and within the society. Whether the volcanic events had a strong or weak socioeconomic effect depended on various factors, such as the prevailing agro-ecosystem, resource availability, material capital, physical and immaterial networks, and institutional practices. These factors influenced societal vulnerability and resilience to cold pulses and associated harvest failures. This paper proposes that, besides detecting coinciding human calamities, more careful investigation at the micro-regional scale has a clear added value as it can provide deeper understanding of why and among whom the distal volcanic eruptions resulted in different societal impacts. Such understanding, in turn, can contribute to interdisciplinary research, advise political decision-making, and enhance scientific outreach.